Case report: Microangiopathic hemolytic anemia and thrombocytopenia in a child with Brucella infection - Alkhunein, Atheer; Albraikan, Ahmed; Alayed, Maria; Althaqafi, Wesam; Alharbi, Musaed (Frontiers in Pediatrics, 2023)
Thrombotic thrombocytopenic purpura (TTP) is a diffused microvascular occlusive disorder characterized by microangiopathic hemolytic anemia (MAHA), thrombocytopenia, and ischemic organ dysfunction. In addition, this condition has been linked to an absence or dysfunction of ADAMTS13. Although TTP can occur due to various factors, such as bacteria, viruses, autoimmune disorders, drugs, connective tissue conditions, and solid tumors, it is a rare hematological complication associated with Brucellosis. We describe the first case of a 9-year-old boy with acquired thrombotic thrombocytopenic purpura (TTP) with undetectable ADAMTS-13 assay secondary to Brucella infection. After initiating antimicrobial therapy, symptoms and laboratory abnormalities improved dramatically, with no recurrence of TTP in subsequent follow-ups.